2021
DOI: 10.12998/wjcc.v9.i35.10816
|View full text |Cite
|
Sign up to set email alerts
|

Association between neutrophil-to-lymphocyte ratio and major postoperative complications after carotid endarterectomy: A retrospective cohort study

Abstract: BACKGROUND Carotid artery cross-clamping during carotid endarterectomy (CEA) may damage local cerebral perfusion and induce cerebral ischemia–reperfusion injury to activate local inflammatory responses. Neutrophil-to-lymphocyte ratio (NLR) is an indicator that reflects systemic inflammation. However, the correlation between NLR and complications after CEA remains unclear. AIM To investigate the association between NLR and major complications after surgery in patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…The NLR re ects the balance of neutrophils and lymphocytes in the body and is more accurate and stable than neutrophils and lymphocytes 29 . In recent years, it has been considered an important in ammatory response marker for diagnosing and evaluating patient prognosis [30][31][32][33] . In this study, we found that the NLR within 48 hours before surgery is also an important predictor of PPCs in children undergoing thoracic surgery requiring OLV, which is consistent with previous reports 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…The NLR re ects the balance of neutrophils and lymphocytes in the body and is more accurate and stable than neutrophils and lymphocytes 29 . In recent years, it has been considered an important in ammatory response marker for diagnosing and evaluating patient prognosis [30][31][32][33] . In this study, we found that the NLR within 48 hours before surgery is also an important predictor of PPCs in children undergoing thoracic surgery requiring OLV, which is consistent with previous reports 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Этиология послеоперационного повышения NT-proBNP в настоящее время неизвестна и может быть многофакторной [59]. Появились также единичные работы по изучении других биомаркеров: соотношение тромбоцитов к лимфоцитам и нейтрофилов к лимфоцитам, показатели системного воспаления [60][61][62], уровень миоглобина [63] были ассоциированы с периоперационными осложнениями при некардиальных операциях. Однако требуются дополнительные более масштабные исследования для изучения возможности их использования в клинике.…”
Section: биомаркерыunclassified
“…The patients mentioned above are at high risk for postoperative AKI, however, our study included a wider range of patients. Unlike these studies, Yu and his colleagues [30] focused on the postoperative NLR and found that NLR within 24 h after surgery was significantly correlated with major postoperative complications in patients undergoing carotid endarterectomy. By using the optimal cut-off value of preoperative NLR obtained in our study, the rate of missed diagnosis is lower, which enables clinicians to be more alert to the occurrence of postoperative AKI in patients, strengthening preoperative prevention and management (e.g., avoid the use of nephrotoxic drugs or angiography) of postoperative renal function problems.…”
Section: Plos Onementioning
confidence: 99%